Noncirrhotic hepatocellular carcinoma: etiology and occult hepatitis B virus infection in a hepatitis B virus-endemic area. (July 2017) - Shim, Chang Woo; Park, Joong-Won; Kim, So Hee; Kim, Jin Sook; Kim, Bo Hyun; Kim, Sung Hoon; Hong, Eun Kyung
Background: Although hepatocellular carcinoma (HCC) usually develops in cirrhotic livers, a minority of cases occur in noncirrhotic livers (NCLs). We investigated etiology, clinicopathological features, and occult hepatitis B virus (HBV) infection (OBI) in patients with NCL HCC in an HBV-endemic area. Methods: A total of 710 patients who underwent resection or transplantation for HCC at the National Cancer Center (NCC), Korea, were enrolled. HCC and fibrosis stage were diagnosed pathologically. Results: A total of 178 patients (25%) did not have cirrhosis (NCL group). The main cause of HCC was HBV infection (77.2%), followed by cryptogenic disease (11.0%). The prevalence of NCL was 19.2%, 32.5%, 50.0%, and 48.7% among patients with HBV, hepatitis C virus (HCV), alcoholic, and cryptogenic disease, respectively ( p < 0.05); corresponding nonfibrosis rates were 8.1%, 0%, 19.0%, and 24.3%, respectively. The NCL group was significantly older, with a larger tumor size, smaller tumor number, lower tumor stage, and more frequent non-HBV etiology. Among non-HBV HCC cases, 130 (80.2%) had antibodies against HBV core (HBc) and 55 (38.5%) had OBI. OBI-positive rates of 0%, 31.8%, and 52.6% were detected among HCV, alcoholic, and cryptogenic HCC cases, respectively. OBI did not correlate with advanced fibrosis. The NCL and liver cirrhosis (LC) groups did not differ in median overall survival. Conclusion: Regardless of etiology, a significant number of HCC patients, including half of nonviral cases, did not have LC. Half of cryptogenic HCC cases had OBI. This study promotes an understanding of fibrosis and OBI among patients with HCC in an HBV-endemic area.